Treatment schemes: from triple therapy to monotherapy in HIV patients: analysis of the efficacy and safety. Issue 2 (12th March 2012) - Solano, B.; Ferrit, M.; Gonzalez, J.; Moya, I.; Sanchez, E.; Gonzalez, C.; Marquez, E.; Gomez, A.I.; Calleja, M.A.; Martinez, F.
Abstract : Background: The simplification of a triple antirretroviral treatment(TAR) to a monotherapy in patients with viraemia controlled by prolonged periods and without previous failure with a protease inhibitor(PI), is an strategy which can decrease the TAR toxicity. Purpose: To analyse the efficiency and safety since the establishment of the naive TAR until the monotherapy with PI. Materials and methods: Retrospective study during 9 months(January-September 2011) of the pharmacotherapeutic history of the HIV patients in treatment with PI in monotherapy during at least 6 months until the naïve TAR which withdrawn medication in the Pharmacy service of the hospital. Efficiency variables: viral load(LV) and CD4 re-count and security variables: appearance of adverse reaction to medication(ARM). Results: Of the 120 patients in triple TAR simplified to monotherapy with PI 19%. 59% men and 41% women. Average age 49 years. 18% started naive TAR with PI in association (18% VL>1000 copies/ml, 45% CD4<350 cells/ml), 50% reduced the VL in a logarithm and 68% of the patients abandoned the TAR. In the following scheme of TAR at 54% were prescribed PI in association (32% VL>1000 copies/ml and 32% VL<50 copies/ml, 40% CD4<350 cells/ml), 77% reduced the VL in a logarithm and for the good control of the disease 50% of the patients were simplified the TAR to PI in monotherapy. To the 91% of the patients lopinavir was prescribed as PI in monotherapy(68% VL<50 copies/ml, 36% CD4<350 cells/ml), 77% maintained the LV undetectable. A total of 26 ARM were detected: 31% of the reverse transcriptase inhibitors(TI) no similar nucleoside, 29% of inhibitors of the TI similar nucleoside, 27% PI. Conclusions: The establishment of the PI in the triple therapy as well as in monotherapy suppose an increase of the efficiency (reduction of the VL and CD4 or undetectable viral load) and safety of TAR